Corporate contributions to society: types and worth of the kinds of collaboration - Valor Martínez, Carmen (Cuadernos de Trabajo Social, 2013)
This paper offers a typology of corporate contributions to society, within the corporate community investments strategy. It also evaluates the different tactics according to several criteria to conclude which one could have the greatest impact on communities. The paper concludes that the types of contribution which are based on the donation of unique resources and capabilities and those stemming from strategic planning, negotiated with stakeholders, are the ones that could have the greatest social impact.